Significance of ferroelectric polarization in poly (vinylidene difluoride) binder for high-rate Li-ion diffusion. (February 2017) - Song, Woo-Jin; Joo, Se Hun; Kim, Do Hyeong; Hwang, Chihyun; Jung, Gwan Yeong; Bae, Sohyeon; Son, Yeonguk; Cho, Jaephil; Song, Hyun-Kon; Kwak, Sang Kyu; Park, Soojin; Kang, Seok Ju
Abstract: An interesting and effective route for improving battery performance using ferroelectric poly(vinylidene difluoride) (PVDF) polymer as a binder material is demonstrated in this work. A ferroelectric PVDF phase developed under the appropriate thermal annealing process enables generation of suitable polarization on active materials during the discharge and charge process, giving rise to longer capacity with lower overpotential at a high current rate. Electrochemical analysis including in situ galvanostatic electrochemical impedance spectroscopy and a galvanostatic intermittent titration measurement revealed that the ferroelectric binder effectively reduced Li-ion diffusion resistance and supported fast migration in the vicinity of active electrodes. Computational results further support that the binding affinity of the ferroelectric PVDF surface is much higher than that of the paraelectric PVDF, confirmed by ideally formed ferroelectric and paraelectric PVDF conformations with Li-ions. Furthermore, we consistently achieved high Li-ion battery (LIB) performance in full cell architecture consisting of a LTO/separator/LFP with a ferroelectric PVDF binder in the anode and cathode materials, revealing that the polarization field is important for fabricating high-performance LIBs, potentially opening a new design concept for binder materials. Graphical abstract: We demonstrate the effect of PVDF polarization in lithium ion battery system. The strong polarization of ferroelectric PVDF binder on the active material enhances the transport of Li-ion during charge and discharge. As results, the Li-ion diffusion by ferroelectric phase leads to excellent rate performance and cycling stability compared to paraelectric PVDF binder. Highlights: The ferroelectric polarization in PVDF binder enhances Li-ions diffusion. Excellent rate performance is demonstrated by β-phase of PVDF binder In depth computational study exhibits the polarization effect of ferroelectric binder in LIB cell.